El acceso a la información ambiental en España: luces y sombras - Casado Casado, Lucía (2013)
This paper analyses the body of law governing the right to access environmental information in Spain, paying particular attention to law 27/2006, of July 18th, which regulates the right of access to information, public participation and access to justice on environmental issues. The analysis focuses on both the active aspects of access to environmental information (the obligation that the public authorities have to collect and communicate environmental information) and the passive aspects (the right to request access to environmental information). Particular attention is paid to the advances made by this legislation and its possible implications, but no attempt is made to conceal the problems of application that it still has to face and the pending challenges.